2017
DOI: 10.35800/jjs.v8i2.17199
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompetensi Aparat Pengelola Dana Desa, Komitmen Organisasi Pemerintah Desa, dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kabupaten Gorontalo

Abstract: Abstract. The accountability of village fund management has become a demand for local government. The existence of this demand results from the implementation of Law No. 6 of 2014 on the Village. The management of village funds in Gorontalo Regency is still far from the expectations. Problems emerging from the accountability of village fund management are related to the competence of village fund management officers, the commitment of village government organizations, and community participation. This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
51
1
94

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(163 citation statements)
references
References 5 publications
(7 reference statements)
17
51
1
94
Order By: Relevance
“…Arumsari et al, (2017) demonstrated that the Village Head who has competence in public communication which takes into account the culture of the community will directly influence the development innovation in the village. Similarly, Munti & Fahlevi (2017) and Mada et al, (2017), and Triyono et al, (2019) found that the competence of the village fund management apparatus has a positive and significant effect on the accountability of village fund management. Therefore it is hypothesized that: H3: Competence of Village Apparatus has a positive influence on village fund management H4: Competence of Village Apparatus has a positive influence on village fund management A sound village fund management potentially has an impact on the attainment of the village autonomy.…”
Section: Research Hypothesesmentioning
confidence: 92%
See 2 more Smart Citations
“…Arumsari et al, (2017) demonstrated that the Village Head who has competence in public communication which takes into account the culture of the community will directly influence the development innovation in the village. Similarly, Munti & Fahlevi (2017) and Mada et al, (2017), and Triyono et al, (2019) found that the competence of the village fund management apparatus has a positive and significant effect on the accountability of village fund management. Therefore it is hypothesized that: H3: Competence of Village Apparatus has a positive influence on village fund management H4: Competence of Village Apparatus has a positive influence on village fund management A sound village fund management potentially has an impact on the attainment of the village autonomy.…”
Section: Research Hypothesesmentioning
confidence: 92%
“…Studies conducted by Mada et al, (2017) and found that community participation had a positive effect on village fund management. In addition, according to Slamet (2003), one of the concepts of participation is the active role of the community in the process of village development from planning, implementation, to evaluation.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Akuntabilitas adalah salah satu prinsip untuk mewujudkan cita-cita tata kelola pemerintahan yang baik (Kurniawan, 2014 (Mada, 2017). Berdasarkan beberapa temuan dan pengamatan atas kasus yang ada, saran yang dapat perlu sampaikan berupa penyempurnaan aplikasi mitra desa sendiri, seperti model aplikasi yang masih satu arah, sehingga dalam penyusunan perencanaan masyarakat belum bisa menyampaikan masukannya secara online, mengingat tidak semua masyarakat akan ada saat desa akan melakukan musyawarah.…”
Section: Peraturan Pemerintah No 60 Tahun 2014 Tentang Dana Desa Sebunclassified
“…This fantastic amount of village funds has been budgeted by the government for Rp127.75 trillion divided into 3 years (2015, 2016, and 2017). Every year, the budgeting for village funds is always increased according to the management carried out by the village government (Mada et al, 2017).…”
mentioning
confidence: 99%